Plaine. - Stein, Sammy; Bretin, Jean-Philippe; Bascouert, Séverine (s.l. : Lagon Revue, 2022)
Angdoo, Jin ; Haifisch, Anna ; Partouche, Élie ; Zertal, Melek ; Butzbach, Louka ; Chemin, Flore ; Sans-Arcidet, Sébastien ; De Jonge, François ; Lemaitre, Paul ; Tezam, Jack ; Son Ni & Chihoi ; Traduttore, Traditore (Clément Faydit & Rozenn Voyer) ; Jacotey, Marie ; Mullican, Matt ; Taylor, Zoë ; Yokoyama, Yuichi ; Bascouert, Séverine ; Gendre, Laetitia ; Boudouard, Denis ; Redon, Julie ; Descamps, Paul ; Coenen, Adriaen ; Robel, Xavier ; Stein, Sammy ; Chernyshova, Daria ; Landrivon, Félicité ; Henni, Bettina ; Orcas, Acacio ; Chris Harnan & Julie Gobled ; Bretin, Jean-Philippe
Artist selection: Sammy Stein ; Graphic design and colour separation: Jean-Philippe Bretin ; Production: Séverine Bascouert & Jean-Philippe Bretin
boek